2019
DOI: 10.1136/emermed-2017-207335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Emergency Medicine Consultants and Clinical Advisors on a NHS 111 Clinical Assessment Service

Abstract: ObjectiveTo compare outcome of clinical advice given by emergency physicians (EPs) versus non-physician clinical advisors (NPCAs) on a UK National Health Service 111 centre.MethodThis was a prospective study conducted between July 2016 and February 2017. We targeted calls in which call handlers using standard NHS 111 clinical decision support software would have advised the caller to attend a hospital ED. These calls were passed to a clinical assessment service (CAS) and reviewed by either an EP (July to Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Existing research has also suggested that the lack of clinical training leading to cautious triaging amongst NHS 111 call handlers may be responsible for high numbers of avoidable ED attendances and ambulance dispatch [8][9][10]. In support of this, many ambulance dispatches did not result in a conveyance to ED, and a large number patients did not attend ED despite being advised to do so (approximately 30%).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has also suggested that the lack of clinical training leading to cautious triaging amongst NHS 111 call handlers may be responsible for high numbers of avoidable ED attendances and ambulance dispatch [8][9][10]. In support of this, many ambulance dispatches did not result in a conveyance to ED, and a large number patients did not attend ED despite being advised to do so (approximately 30%).…”
Section: Plos Onementioning
confidence: 99%
“…Though some clinical advisers are also available to support, particularly with more challenging cases, this staffing decision has received particular criticism, and is suggested to be the cause of increased pressure on emergency services. Studies suggest that those with a clinical background, such as GPs and nurses, tend to be markedly less risk averse in their recommendations to callers [8,9], and paramedics attending patients referred to the ambulance service by NHS 111 have expressed frustration at overly cautious triaging by non-clinical call handlers [10]. Evidence also suggests that callers are more likely to make an avoidable ED attendance if they receive advice only from a call handler and not from a clinical adviser [4], which may compound already cautious triaging.…”
Section: Introductionmentioning
confidence: 99%
“…While the statistical picture about whether actual increases in demand are associated with NHs 111 service use is more nuanced, 28,130 this narrative continues to be a powerful negative message about NHS 111 services and one that could gain further weight as use of NHS 111 online grows. There is one UK study suggesting that clinical call handlers decreases referrals to ED, 131 and this is supported by evidence about Healthdirect that suggests that clinician triaged calls achieve a higher level of appropriate onward referral. 132,133 The interviews did not suggest that there had been a significant shift of demand for other services related to NHS 111 in general, or NHS 111 online specifically.…”
Section: Discussionmentioning
confidence: 97%